The effect of estrogen on the gnads and on in vitro conversion of androstenedione to testosterone, 11-ketotestosterone, and estradiol-17ß in Sparus aurata (Teleostei, Sparidae) - Condeça, João B. (2014)
The effects of estrogen on gonad morphology and steroidogenesis of sea bream, Sparus aurata, a protandrous hermaphrodite teleost, were investigated. Fish were treated in winter/spring for different periods with 17aethynylestradiol (ethE2; experiment 1) and in summer with two doses of estradiol-17b (E2; experiment 2). Estrogen was more effective in summer. Its main effect on the gonad was inhibition of testicular growth and of male germ cell development beyond the spermatogonia stage, including mitosis. The effect of estrogen on ovarian development was slight and only apparent at the end of experiment 2 in the higher dose group. Gonadal fragments were incubated at different times during treatment with androstenedione and the output of testosterone (T), estradiol (E2), and 11-ketotestosterone (11KT) was measured by radioimmunoassay. T and E2 production was inversely correlated with the proportion of testicular tissue (and positively with ovarian tissue) in the gonad in experiment 2. However, the production of 11KT was not correlated with any type of tissue, possibly because of further metabolism. Inhibition of testicular development by estrogen was also associated with higher output of steroid conjugates.